PENYIDIKAN PELAKU TINDAK PIDANA PENYELUNDUPAN MANUSIA BERDASARKAN KITAB UNDANG-UNDANG HUKUM ACARA PIDANA OLEH KEPOLISIAN RESOR KOTA PEKANBARU - John Nardy; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Human smuggling (people smuggling) occurred in the city of Pekanbaru, this is because pekanbaru a place where the border regions directly adjacent to some neighboring countries such as Singapore and Malaysia, so it becomes a shortcut or transit for human trafficking, human smuggling that occurred during this The Regional Police Pekanbaru city there is only one case that happened on 28 August 2014 performed by supiono as criminal human smuggling that took seven foreign nationals who come from Afghanistan, the Pekanbaru City Police managed to capture supiono to conduct raids The combined so terbongkarlah case of human smuggling. This type of research is quite juridical sociological research, because in this study the authors directly conduct research on locations or places studied in order to give a complete and clear picture of the problems examined. This research was conducted at the Regional Police Pekanbaru, while the sample population is a whole party with regard to the issues examined in this study, the source of the data used primary data and secondary data, while data collecting technique in this research is done with interviews / interview and study data using deductive method is to analyze the problems of a general nature subsequently withdrawn padfa specific conclusions based on existing theories. Results of the discussion of this paper is, first, that the crime of human smuggling in the region pekanbaru town in handling the Immigration and Police are not yet optimal, secondly, the lack of public knowledge about immigrants and the danger of human trafficking crimes, criminals organized human smuggling , the apparatus is less responsible, third, the efforts made in addressing the crime of human smuggling to act effectively and efficiently in handling criminal cases of human trafficking, conduct raids combined with other law enforcement officers on the borders or ports of existing.